Gambaran Gaya Hidup Remaja Yang Mengonsumsi Konten Budaya Pop Korea di Youtube - Yang, Angelina Elni; Utami, Lusia Savitri Setyo (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Korean pop culture or Hallyu is growing rapidly, including in Indonesia. The majority of Korean pop culture fans in Indonesia come from teenagers aged 12-20 years. It is also during adolescence that an individual forms and seeks their identity, one of which is by imitating what they see. Increasingly sophisticated technology facilitates more and more new media content for teenagers to use as a reference in building a lifestyle, one of which is on YouTube. The purpose of this study is to find and describe how the lifestyles of mid-teens aged 14-17 years are exposed to Korean pop culture content on YouTube. In the Uses and Gratification Theory, youth as audiences are seen as active audiences who can choose for themselves what content they want to consume and how exposure to this content has implications for their lifestyle. This study uses a qualitative research approach with phenomenological methods. The research data were obtained through interviews and observations of six informants, documentation and literature studies. The results of this study state that with their motivation and needs, teenagers use selective attention to choose the content they want to watch. The response given by teenagers to the same content also depends on the perspective of each individual. That response is reflected in the activities, interests and opinions of adolescents and shapes their lifestyle. Budaya pop Korea atau Hallyu berkembang sangat pesat secara global, termasuk di Indonesia. Mayoritas penggemar budaya pop Korea di Indonesia datang dari remaja berusia 12-20 tahun. Pada masa remaja jugalah seorang individu membentuk dan mencari jati diri mereka, salah satunya dengan meniru apa yang mereka lihat. Teknologi yang kian canggih memfasilitasi semakin banyak konten new media untuk remaja jadikan sebagai referensi dalam membangun gaya hidup, salah satunya di YouTube. Tujuan dari penelitian ini adalah untuk mengetahui dan mendeskripsikan bagaimana gaya hidup remaja pertengahan usia 14-17 tahun yang diterpa konten-konten budaya pop Korea di YouTube. Dalam Teori Uses and Gratification, remaja sebagai audiens dilihat sebagai khalayak aktif yang dapat memilih sendiri konten apa yang ingin mereka konsumsi dan bagaimana terpaan konten tersebut berimplikasi pada gaya hidup mereka. Penelitian ini menggunakan pendekatan penelitian kualitatif dengan metode fenomenologi. Data penelitian diperoleh melalui kegiatan wawancara dan observasi pada enam informan, dokumentasi dan studi literatur. Hasil penelitian ini menyatakan bahwa dengan dorongan motivasi dan kebutuhannya, para remaja menggunakan selective attention untuk memilih konten yang ingin mereka tonton. Respon yang diberikan remaja pada konten yang sama juga bergantung pada perspektif masing-masing individu. Respon itu tercermin dalam aktivitas, minat dan opini remaja dan membentuk gaya hidup mereka.